DEVELOPMENT OF MEDIA LITERACY OF STUDENTS IN THE PROCESS OF STUDYING INFORMATICS AND INFORMATION TECHNOLOGIES IN OUR COUNTRY (Web of Teachers: Inderscience Research, 2024)
In our society, the information process expands the boundaries of communication between people. Communication tools have been proven to be an integral part of the development of civilizations. Currently, information technologies, various projects, forms of distance education, and electronic textbooks are entering modern schools. The modern world is becoming more beautiful with the world of mass communication. This article aims to increase the level of media literacy of students and teachers through the integration of media education and the science of informatics and information technologies.